A REVIEW: EXPERIMENTAL ANIMAL MODEL OF HELICOBACTER PYLORI IN 2018-2023 - Cheardi, Natallensi Deara (Jurnal Biosains Pascasarjana, 2025)
H. pylori is a Gram-negative bacterium that has colonized the stomachs of approximately 50% of the human population worldwide. H. pylori is a major pathogen associated with gastrointestinal diseases, including gastritis, peptic ulcers, and gastritis, gastric adenocarcinoma, and mucosa-associated lymphoid tissue (MALT). To study the pathogenesis, prevention and therapy of H. pylori infection, ideal, safe and stable animal model experiments are needed. Therefore, in this text we summarize several important aspects in successfully creating experimental animal models of H. pylori. The method used is literature study through two electronic databases, namely Sciencedirect and Pub Med. A total of 50 articles were used in this study. Full text assessment was carried out according to inclusion and exclusion criteria. The C57BL/6 and BALB/c animal models are capable of producing gastritis, metaplasia and hyperplasia and rarely produce cancer, while Mongolian gerbils and transgenic mice are considered more susceptible to creating cancer models. The strains commonly used in research on H. pylori infection are SS1 and PMSS1 because they are considered to be CagA-positive. The non-invasive method for confirming H. pylori that is most often used in experimental animal models is the ELISA serological test, while the invasive methods that are often used are RUT and H&E and other additional staining.